2019
DOI: 10.12659/msm.916731
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of MiR-129-5p on Acute Spinal Cord Injury Rats

Abstract: Departmental sources Background: Spinal cord injury (SCI) is a severe devastating condition associated with serious disability and neurologic deficits. Aberrant micro RNA (miRNA) expression has been related to a variety of central nervous system diseases including SCI. In the present study, we aimed to discover the role of miR-129-5p on SCI. Material/Methods: An acute SCI rat model was induced, following the modified Allen method. A total of 36 rats were randomly assigned into 4 groups (n=9 in every group): Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…MiR-129-5p participates in regulating the proliferation, migration, and invasion of retinoblastoma cells and affects spinal cord injury [13,14]. In a study on the regulation of osteogenic differentiation, Valenti et al [15] found that physical exercise modulates miR-129-5p expression in progenitor cells and thus promotes osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-129-5p participates in regulating the proliferation, migration, and invasion of retinoblastoma cells and affects spinal cord injury [13,14]. In a study on the regulation of osteogenic differentiation, Valenti et al [15] found that physical exercise modulates miR-129-5p expression in progenitor cells and thus promotes osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a serious complication of spine injury, putting patients in debilitating pathological conditions physically and psychologically, and may cause huge economic challenges to society [1][2][3]. SCI leads to physical damages, including infarction of the spinal cord, dyskinesia, and sensory deficits in the area below the injury, muscle wasting, chronic pain, and paralysis [4,5], resulting in acceleration of tissue edema, neural cell apoptosis, and the inflammatory cytokine release [6].…”
Section: Introductionmentioning
confidence: 99%
“…21,24 Particularly, mimic miRNA-129-5p (miR-129) has received signicant attention as it can suppress cell apoptosis and microglia-induced inammatory response as well as polarize their phenotype through highmobility group protein B1 (HMGB1)/toll-like receptor4 (TLR4)/ NF-kB and leucine-rich alpha-2-glycoprotein (LRG1)/p38 mitogen-activated protein kinases (MAPK) pathways. [25][26][27][28] As a well-known maker of inammatory mediators and cancer therapy, HMGB1 is a direct target of miR-129. [29][30][31] Moreover, HMGB1 is passively released by necrotic and/or stressed cells as well as by immune cells including activated microglia.…”
Section: Introductionmentioning
confidence: 99%